Break-even Point and Margin of Safety Analysis In Sugarcane cultivation of Farmers With the introduction of agricultural machinery to be used in Nakhon Sawan Province - sansong, panthip (Journal for Developing the Social and Community, 2020)
The objectives of this research were threefold: First, to examine the general situations and the concerning data in terms of using the sugarcane agricultural machine of farmers; Second, to analyze the break-even point and the safety benefit margin of farmers who used the sugarcane agricultural machine for cultivation; and Third, to analyze the basic factors affecting the sugarcane plant of farmers. Three hundred and eighty-four sugarcane farmer questionnaires were collected by the multi-stage random sampling technique. The following statistics were employed: frequency, percentage, means, standard deviation, and the administrative accountancy and principle criterion with occurred behavioral style. Research results found that 1. Most sugarcane farmers were as male (58.30%), aging 41– 45 years-old (26.60%), highest education - sixth grade (39.90%), only one occupation - sugarcane plant (75.80%), sugarcane plant experience during 5 -10 years (46.60%), most financial sources from themselves (39.63%), having moderate area 60-199 Rai for plant (70.30%), most sugarcane as a type of Early rain sugarcane outside the irrigation area (66.15%) and most of new sugarcane (76.38%), every farmers took the agricultural machine for planting (100%), most some agricultural machine invested by farmer and some aspects cooperating with agency (94.33%). Also, an investment for permanent assets or agricultural machines were the average mean as 300,000 Baht. 2. Capital investment and taking the agricultural machine for planting, it revealed that capital divided by behaviors were as follows: Average of adjusted capital per rai as 11,381.08 Baht, consisted of (1) raw materials as sugarcane nursery plants 1,763.18 Baht per Rai; (2) presume labor costs, such as ground preparation 1,360.20 Baht per Rai, nursery plant preparation 367.14 Baht per Rai, plant employment 635.14 Baht per Rai, caring employment 542.36 Baht per Rai, and harvest and transportation prices by using the sugarcane cut off machine 5,203.20 Baht per Rai; (3) other expenses, such as fertilizer 1,026.28 Baht per Rai; drug for get rid of weeds ang bugs 350.16 Baht per Rai; and fuel oil 133.42 Baht per Rai; average of constant capital 1,791.46 Baht per Rai, Rent 1,203.16 Baht per Rai, such as depreciate in value of machines 588.30 Baht per Rai; summary: average of the total capital 13,172.54 Baht per Rai or the capital mean as 810.12 Baht per sugarcane ton. It was also found that the benefits of products in the area 1 Rai had the products 16.26 tons and gave benefit 880.34 Baht per ton at the average of sweet 12.17 C.C.S. (average income as 14,314.33 Baht per Rai, net profit 1,141.79 Baht per Rai). Also, it was found that the plant area 102.27 Rai, break-even point was as 1,662.97 tons or 1,428,571.43 Baht. In this case if farmers could increase products as 18 tons per Rai, they would receive the margin of safety at 9.42 percent. 3. Basic factors affecting the sugarcane planting, it revealed that these aspects had crucial effects on sugarcane planting: men at moderate, budgeting at high, agricultural machine at moderate, and management at moderate levels, average means as 3.15, 3.70, 3.24, and 2.80, respectively.